Implementasi Konsep Dynamic Pada Interior Creative Industry Co-working Space di Surabaya - Sherliana Jovita Wijaya; Ronald Hasudungan Irianto Sitindjak; Linggajaya Suryanata (Intra, 2017)
Humans in working activities or doing tasks require a comfortable atmosphere and conducive course. Co-working space is a common office concept for start-ups especially for young people who are just starting their business. This design aims to create a Creative Industry Co-working Space for creative industries that create a productive work atmosphere as well as effective and efficient and become an object of interest by start-ups in Surabaya.The method used in this design is through the process of design thinking starting from the stage of understanding is to understand the object of design by looking for literature as a theoretical basis. Followed by observe with field studies of similar objects. Then proceed with an ideate that starts to go into concept and schematic design. After that the selected designs are developed and presented through work drawings and presentation mockups at the prototype stage. After that the test is done as the final evaluation of the supervisor and examiner.Interior Design Creative Industry Co-working Space is designed by creating a dynamic and conducive working environment, which encourages users to always move in developing their ideas. Through a modern design and simple, but stay elegant and comfortable. Available support facilities such as phone booth, coffee corner for leisure, lounge, self pantry, reading spot, gaming room and outdoor communal space for assembled area.